Recent changes in the epidemiology of Neisseria meningitidis serogroup W across the world, current vaccination policy choices and possible future strategies - Robert Booy; Angela Gentile; Michael Nissen; Jane Whelan; Véronique Abitbol (Taylor & Francis Group, 2019)
Invasive meningococcal disease (IMD) is a serious disease that is fatal in 5-15% and disabling in 12-20% of cases. The dynamic and unpredictable epidemiology is a particular challenge of IMD prevention. Although vaccination against meningococcal serogroups A (MenA), MenC and, more recently, MenB, are proving successful, other serogroups are emerging as major IMD causes. Recently, surges in MenW incidence occurred in South America, Europe, Australia and parts of sub-Saharan Africa, with hypervirulent strains being associated with severe IMD and higher fatality rates. This review describes global trends in MenW-IMD epidemiology over the last 5-10 years, with emphasis on the response of national/regional health authorities to increased MenW prevalence in impacted areas. Several countries (Argentina, Australia, Chile, the Netherlands and UK) have implemented reactive vaccination campaigns to reduce MenW-IMD, using MenACWY conjugate vaccines. Future vaccination programs should consider the evolving epidemiology of MenW-IMD and the most impacted age groups.